Differences in Students' Concept Understanding With the Probem Based Learning Model Through a Scientific Approach in Grade V Elementary School Students - Marta Siska Jamina Hia; Lisa Virdinarti Putra (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to determine the effect of the Problem Based Learning model through a scientific approach on the conceptual understanding of V grade students at SD Negeri Karangjati 04. The research method used is a quantitative method with a Quasi Experimental Design (Non Equivalent Control Group Design) . The population in this study were all students of SD Negeri Karangjati 04. The research sample was class VA as the Experimental class while class VB as the Control class. Data collection techniques used test techniques through pretest and posttest and non-test techniques including observation questionnaires, documentation, and unstructured interviews. Data analysis was carried out using normality tests, homogeneity tests, independent sample tests t-test. The results of the study indicate that the use of problem based learning models through a scientific approach can improve the ability to understand concepts between the experimental class and the control class, as evidenced by the results of the independent sample t-test showing a significant value of 0.000 <0.05 and the results of the simple linear regression test showing a significant value of 0.009 <0.05. Based on the results of the study, it can be concluded that the use of problem based learning models through a scientific approach can improve students' ability to understand concepts.